Презумпция невиновности - Леонов Николай Иванович (Перехват, 1996)
Экземпляры: Ф22 (20170713) / Инвентарный номер: 54211 / Цена: 80.00 / Сис.шифр: Р2 / Авт.знак: Л 47 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6